2017
DOI: 10.1002/adfm.201701613
|View full text |Cite
|
Sign up to set email alerts
|

Laser‐Induced Localized Growth of Methylammonium Lead Halide Perovskite Nano‐ and Microcrystals on Substrates

Abstract: Laser-Induced Localized Growth of Methylammonium Lead Halide Perovskite Nano-and Microcrystals on SubstratesStable MAPbBr 3 crystals with different sizes are successfully localized on a flat substrate via laser-induced heating of the liquid precursors. By adjusting the infrared laser parameters, luminescent arrays and photoconductive wires are grown on-site. This technique can be used to guide the writing of other patterns for specific functionalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 52 publications
(54 reference statements)
0
55
0
Order By: Relevance
“…[27] As shown in Figure 1c, the bare glass showed a peak temperature of 433C due to its low photo-thermal conversion. [18,28] For the ITO-glass, the peak temperature was boosted to 584°C due to the photon-induced excitation of the free charge carriers in ITO resulting in instantaneous local heating. [28] Adding a thin amorphous compact TiO2 film (50 nm) on ITO-glass did not increase the peak temperature.…”
Section: Figure 1amentioning
confidence: 99%
See 2 more Smart Citations
“…[27] As shown in Figure 1c, the bare glass showed a peak temperature of 433C due to its low photo-thermal conversion. [18,28] For the ITO-glass, the peak temperature was boosted to 584°C due to the photon-induced excitation of the free charge carriers in ITO resulting in instantaneous local heating. [28] Adding a thin amorphous compact TiO2 film (50 nm) on ITO-glass did not increase the peak temperature.…”
Section: Figure 1amentioning
confidence: 99%
“…Increasing the power density also led to an increase in recorded temperature on the TiO2 surfaces from 513 C to 595C as shown in Figure 5b. Following irradiation by the laser pulse the sample was found to remain at a temperature, T > 450C for 18.9 s and 39.5 s and T > 280C for 66.3 s and 82.9 s for the 86 W cm -2 and 107 W cm -2 pulses, respectively. Since Raman spectra showed that the organic binders were completely removed, and crystallization of the compact TiO2 films occurred for all three laser conditions as shown in Figure S4 and S5, the difference in PCEs is believed to be related to the difference in the degree of interconnections between the TiO2 nanoparticles.…”
Section: Figure 1amentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, lead halide perovskites have attracted much attention due to their exceptional electronic and optical properties and low-cost fabrication and solution processability. [1][2][3][4][5] In addition to the typically cubic, three-dimensional nanocrystals, structures with lower dimensionality such as perovskite nanosheets, nanowires, and the so-called 0D perovskites have been fabricated through simple modifications of wet chemistry fabrication protocols. [6][7][8][9] Among the low-dimensional perovskites, two-dimensional (2D) layered crystals have been the focus of several studies, given their bright emission, possible white fluorescence, and, in particular, their environmental stability.…”
Section: Introductionmentioning
confidence: 99%
“…This drawback was addressed by using N ‐methylformamide (NMF) to serve as the solvent and the source of MA ions. [ 94 ] The femtosecond laser with a repetition rate of 80 MHz would induce localized heat on the Si substrate to over 100 °C in seconds through multiphoton absorption. By tuning the laser scanning speed and power density, stable arrays or lines formed by MAPb X 3 microcrystals can be achieved without any other steps.…”
Section: Perovskite Patterning Technologiesmentioning
confidence: 99%